PENGAMBILAN KEPUTUSAN PASANGAN USIA SUBUR MENGGUNAKAN KONTRASESPSI IUD - Nina Primasari (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Background : WHO data shows that the failure rate of birth control pills is about 90 per 1,000 users and injectables 60 per 1,000 users while the IUD failure rate is only 8.5 people out of 1,000 users. The use of hormonal birth control in the long term can cause side effects that will have an impact 10 years later such as osteoporosis and cancer while the side effects IUD caused can be overcome properly and do not have excessive impacts such as hormonal birth control. Based on data from the CDC, look at the level of effectiveness for use of the top birth control methods used in different regions. In certain areas of Asia, female sterilization (99.5% effective) is no longer the most popular method of birth control. In contrast, IUDs (99.2% to 99.98% effective) are the top methods in China, but in Indonesia there has been a change from the most users of pills to injections (32.6%). Objectives : This study was conducted to get an idea of the decision-making of IUD contraceptive methods by Couples of Childbearing Age. Research Methods: This study uses qualitative methods, a type of RAP (Rapid Assessment Procedures) research by conducting in-depth interviews (Indepth interviews). Data collection is carried out by researchers with the collection of primary data and secondary data. Previous interview and observation guidelines have been conducted triangulation tests with 3 speakers, consisting of Couples of Childbearing Age who do not use IUD birth control, KIA midwives and Cadres. Results and Discussions : The results of the study show that the husband's support for IUD birth control is still less desirable because the husband considers it can cause not having children, fear of having an effect on the wife, the assumptions from the environment about the IUD birth control so that the husband does not support the use of IUD birth control and switch to using birth control that is comfortable and suitable for the mother and husband. However, to use other birth control husband support is very large from starting to take decisions together, and responsible to the results of the chosen decision. Conclusion and Advice : Factors that influence the decision-making of IUD contraceptive methods by couples of childbearing age are influenced by internal and external factors. The role of the midwife provides counseling and counseling to husbands and wives for an understanding of contraception. Not only wives, husbands also have a big share to determine what contraceptive they will choose.